Optimalisasi Timbunan Banko Barat Pit-1 Timur Tahun 2014 di PT. Bukit Asam (Persero), Tbk Unit Penambangan Tanjung Enim - Andre Gustian; Bambang Heriyadi; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2015)
Site selection is influenced by several factors like the volume of material to be deposited, whether or not coal seams underneath, distance and topography. The amount of material that must be stockpiled on site Disposal Dumping Material (heap) the longer the sums are increasing, This goes along with the progress of mining.Considering the increasing number of opening new mines in PT. Bukit Asam (Persero), Tbk, so that the soil exposition needs to be managed properly. Required to standardize the management of the soil pile, so the pile area can be used optimally.From the direct she ar strength test results data showed parameter are cohesion ( C ) = 36.24 kPa, friction angle (f) = 16.72˚, and wet density (gw) = 19.36 kN/m3Based on simulation results F Kon a pile Banko Barat Pit-1 Timur derived the optimization of simulation (Geostudio/ Slope W 2007) sho thatby adding 7 ladder more with 6 meter high slope, angle ofa single slope 1: 2 and 25 meter of wide berm is still safe.